Reliability of the Method for Establishing Causation between Electrical Circuit Overload and Fire Ignition - I. S. Taubkin; A. R. Saklantiy (Теория и практика судебной экспертизы)
The article presents an analysis of the Russian Federal Centre of Forensic Science of the Russian Ministry of Justice publication ‘Expert study of copper conductors withdrawn from the site of a fre. Learner’s guide’ 2015. It is shown that this Learner’s guide cannot provide the method of conducting forensic fre examination and methodological references of the Ministry of Internal Aﬀairs and the Ministry of Emergency Situations on establishing a causal relationship between emergency modes in copper wiring and fre ignition require considerable refnement.